PEMBERIAN BIOCHAR TEMPURUNG KELAPA DAN PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN HASIL KUBIS BUNGA (Brassica oleraceae var. botrytis L.) PADA TANAH GAMBUT PEDALAMAN - Tribuyeni Tribuyeni; Syahrudin Syahrudin; Widiastuti L (AgriPeat, 2016)
The purpose of research was to find the interaction of biochar coconut shell applying and liquid organic fertilizer Nasa on growth and yield cauliflower on peat soil. Research was using completely randomized design (CRD) with two factors. The first factor was the provision of biochar coconut shell (B) which consists of three levels, namely: 0, 4,and 6 t ha-1. The second factor was the concentration of liquid organic fertilizer Nasa (N) which consists of 4 levels, namely:0, 4, 6, and 8 cc.L-1 water. Variables measured were : plant height, number of leaves, leaf area, flower diameter and weight of flowers.The results showed that there was an interaction between the provision of biochar coconut shell and liquid organic fertilizer on plantheight, number of leaves, leaf area, flower diameter and weight flower. Giving biochar coconut shell at 6 t ha-1 and liquid organic fertilizer Nasa 8 cc.L-1 water, coud promote the growth and yield of cauliflower with the best result of flower weight at 235.18 g.plant-1.